The art of perspective the ultimate guide for artists in every medium - Metzger, Philip W. 1931- (North Light Books, 2007)
"If the concept of perspective makes you think of confusing angles, fancy measuring gadgets and complicated theories, get ready for a very pleasant surprise. In this comprehensive guide, Phil Metzger demystifies perspective, presenting it simply as a matter of mimicking the way we see--like the way a distant mountain appears blue, or a road seems to narrow in the distance. The art of perspective offers simple but powerful techniques for achieving a convincing illusion of depth and distance, whether it's a few inches in a still lifer or miles in a landscape." -- Provided by publisher